(untitled) (Jurnal Geomine, 2015)
Tools unloading and conveyance is a very influential tool in achieving production targets. The purpose of this study was conducted to determine facto productivity and the factors that affect the productivity of the tool load and conveyance in order to achieve production targets. The data collection method that researchers use research is descriptive quantitative data used in this research is data work efficiency, fill factor, swell factor, cycle time, productivity tools and unloading, and productivity of conveyance then synthesized to obtain the value of productivity. Where the production capability is determined by calculation teoriris is 436.551 tons / hour x 7 hours = 3055.857 tons / shift, because there are three shifts a day, the resulting production dala one day was 3055.857 tons / shift x 3 shifts = 9167 , 571 Ton / day. Facto-inhibiting factors include hauling road conditions that have terrain climbing and winding, queuing at the stockpile area, harmony and unloading tools and conveyances are less than ideal, the loading pattern. As for how that needs to be done to meet the production target road widening, alteration pattern of loading, unloading and harmony tool conveyance, blasting is carried out to produce materials that easily processed by the crusher in order to avoid queuing at the stockpile area. Target production is not achieved only produce 9167.671 tons / day which is targeted productiontarget of 10,000 tons / day, the need for road widening sebejar 6 meters in order to work optimally, changes in the loading pattern of bottom loading using double back up, blasting results must produce if the material is easy on the crusher so that no overlapping conveyance diarea stockpile and can work optimally.